2009
DOI: 10.5194/bg-6-1975-2009
|View full text |Cite
|
Sign up to set email alerts
|

Sensible and latent heat flux from radiometric surface temperatures at the regional scale: methodology and evaluation

Abstract: Abstract. The CarboEurope Regional Experiment Strategy (CERES) was designed to develop and test a range of methodologies to assess regional surface energy and mass exchange of a large study area in the South-Western part of France. This paper describes a methodology to estimate sensible and latent heat fluxes on the basis of net radiation, surface radiometric temperature measurements and information obtained from available products derived from the Meteosat Second Generation (MSG) geostationary meteorological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…While comparing ground eddy covariance fluxes with aircraft fluxes over diverse European regions, Gioli et al (2004) found the value of H at an average height of 70 m was 35 % less that those at ground level, whereas no such trend in λE was observed. Similarly, Miglietta et al (2009) found H lapsed by 36 % as one moved from the surface to a height of 100 m. The same behaviour has also been frequently observed in both airborne and ground-based eddy covariance measurements in the USA (e.g. Desjardins et al, 1992) and Europe (Torralba et al, 2008;Miglietta et al, 2009).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…While comparing ground eddy covariance fluxes with aircraft fluxes over diverse European regions, Gioli et al (2004) found the value of H at an average height of 70 m was 35 % less that those at ground level, whereas no such trend in λE was observed. Similarly, Miglietta et al (2009) found H lapsed by 36 % as one moved from the surface to a height of 100 m. The same behaviour has also been frequently observed in both airborne and ground-based eddy covariance measurements in the USA (e.g. Desjardins et al, 1992) and Europe (Torralba et al, 2008;Miglietta et al, 2009).…”
Section: Discussionsupporting
confidence: 49%
“…Similarly, Miglietta et al (2009) found H lapsed by 36 % as one moved from the surface to a height of 100 m. The same behaviour has also been frequently observed in both airborne and ground-based eddy covariance measurements in the USA (e.g. Desjardins et al, 1992) and Europe (Torralba et al, 2008;Miglietta et al, 2009). Because of the differing lapse properties of λE and H , one would imagine (satellite) should, on average, be more than (tower), which, despite being somewhat uncertain, is what we observe both in Figs. 2 and 3a.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al, 2007) to the most complex models (e.g. Rodell et al, 2004;Albergel et al, 2010) have been investigated and applied to a variety of spatial scales, from local and regional (Bastiaanssen et al, 1998;Su, 2002;Stisen et al, 2008;Miglietta et al, 2009) to global scales (Jiménez et al, 2009). Most of these studies are made for research purposes and use only selected datasets.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that surface temperature is determined by radiation flux, sensible heat flux, latent heat flux, specific heat of soil layer, and thermal conduction system, while surface temperature also affects sensible heat flux and latent heat flux (Miglietta et al 2009). Part of net radiation flux is absorbed by the earth's surface, which further influences latent heat flux and sensible heat flux, with the rest transformed into soil and soil heat flux.…”
Section: Urban Area Change From 2010 To 2030mentioning
confidence: 99%